Lupine protein hydrolysates decrease the inflammatory response and improve the oxidative status in human peripheral lymphocytes. (December 2019) - Cruz-Chamorro, Ivan; Álvarez-Sánchez, Nuria; Millán-Linares, María del Carmen; Yust, María del Mar; Pedroche, Justo; Millán, Francisco; Lardone, Patricia Judith; Carrera-Sánchez, Cecilio; Guerrero, Juan Miguel; Carrillo-Vico, Antonio
Abstract: Although cell-free systems and immortalized cell lines have been used to demonstrate the potential health benefits of lupine proteins and peptides, no study has examined the effects of lupine protein hydrolysates (LPHs) on the immune and oxidative responses of non-immortalized human cells. Therefore, the aims of this study were to evaluate the effects of the in vitro administration of LPHs from Lupinus angustifolius on the immunological and oxidative statuses of human peripheral blood mononuclear cells (PBMCs) from 53 healthy donors. LPHs reduced PBMCs proliferation and the levels of Th1, Th9 and Th17 pro-inflammatory cytokines without being cytotoxic. LPHs also skewed the pro-/anti-inflammatory balance towards a Th2 protective response. Additionally, LPHs increased superoxide dismutase and catalase activities, and the total antioxidant capacity (TAC). This study is the first to show that LPHs reduce T cell inflammatory responses and improve the anti-inflammatory/pro-inflammatory cytokine balance and the TAC by PBMCs. Thus, LPHs may represent an effective option for developing nutritional strategies to prevent pathologies with underlying inflammation and oxidative stress. Graphical abstract: Unlabelled Image Highlights: LPHs reduce human PBMCs proliferation. Th1, Th9 and Th17 inflammatory responses are decreased in LPHs treated PBMCs. LPHs skew the pro-/anti-inflammatory balance towards a protective phenotype. The total antioxidant capacity is improved in LPHs-treated PBMCs.